2019
DOI: 10.1155/2019/6936175
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Profiles Reveal That ADCYAP1 Serves as Key Molecule in Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) refers to the condition which shows abnormal glucose metabolism that occurs during pregnancy, while normal glucose metabolism before pregnancy. In the present study, a novel analytical procedure was used to explore the key molecule of gestational diabetes mellitus. First, the weighted pathway model was carried out subsequently to eliminate the gene-overlapping effects among pathways. Second, we assessed the enriched pathways by a combination of Fisher’s t-test and the Mann–W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Adenylyl cyclase is a key enzyme of the G-protein coupled signaling pathway that is involved with a plethora of hormones, including insulin. In a 2019 epigenetic profiling manuscript, placental samples from 82 patients were screened for differentially methylated genes and 3 molecules were identified: CAMK2B, ADCYAP1, and KCNN2 [14] In addition, a smaller scale study with 24 patients also identified CAMTA1, a transcriptional activator involved in insulin secretion and regulation to be differentially methylated. More specifically, there was decreased methylation of CAMTA1 in the peripheral blood of GDM patients compared to control; further suggesting that disruption of insulin regulation and function is partially responsible for GDM development [15].…”
Section: Insulin Metabolismmentioning
confidence: 99%
“…Adenylyl cyclase is a key enzyme of the G-protein coupled signaling pathway that is involved with a plethora of hormones, including insulin. In a 2019 epigenetic profiling manuscript, placental samples from 82 patients were screened for differentially methylated genes and 3 molecules were identified: CAMK2B, ADCYAP1, and KCNN2 [14] In addition, a smaller scale study with 24 patients also identified CAMTA1, a transcriptional activator involved in insulin secretion and regulation to be differentially methylated. More specifically, there was decreased methylation of CAMTA1 in the peripheral blood of GDM patients compared to control; further suggesting that disruption of insulin regulation and function is partially responsible for GDM development [15].…”
Section: Insulin Metabolismmentioning
confidence: 99%
“…The GDM is an extremely complicated pathophysiological process and controlled by various genes and signaling pathways. Genes such as PVT1 [10], IL-6, IL-10, and TNF-α [11], CAPN10 [12], ADCYAP1 [13] and ABHD5 [14] are associated with GDM. Signaling pathways such as PI3K/AKT signaling pathway [15], AMPK signaling pathway [16], vitamin D signaling pathways [17], TLR4/NF-kappaB Signaling Pathway [18] and AGEs-RAGE signaling pathway [19] are linked with GDM.…”
Section: Introductionmentioning
confidence: 99%